Pemetaan Potensi Pajak Daerah di Kabupaten Sikka Tahun Anggaran 2020-2021 - Fransiska Irmawanti Usnaat; Henrikus Herdi; Paulus Libu Lamawitak (Universitas Maritim AMNI Semarang, 2023)
The formulation of the problem in this research is how does the mapping of local tax potential in Sikka Regency based on leading sources, potential sources, developing sources, and underdeveloped sources? This research aimed to determine the mapping of local tax potential in Sikka Regency based on leading, potential, developing, and underdeveloped sources. Research methods used in data collection were interviews and documentation. The data analysis technique was quantitative descriptive analysis using Klassen Typology analysis. The results of the research concluded that of the ten sources of local tax revenue in Sikka Regency included in quadrant I (leading sources) there were no sources of local tax revenue included in the leading sources because the ten sources of local tax revenue lack of potential revenue and the ability to manage high potential. Quadrant II (developing sources) were entertainment tax and billboard tax, where the government has high revenue potential but had the ability to manage low potential. Quadrant III ( potential sources) were road lighting tax, rual-urban land and building tax, and acquisition duty on land building where the government had low potential but had a high capacity to manage. Those included in quadrant IV (underdeveloped sources) were hotel tax, restaurant tax, parking tax, groundwater tax, and non-meltallic mineral and rock tax. That five sources were lack potential revenue and the ability to manage high potential.